Análise das manifestações patológicas nas fachadas do hospital Casa de Saúde de Santa Maria, RS - Bernardi, Danieli Faccin (2021)
Among the expressive number of material goods left by the Rio Grande do Sul Railroad Consumption Cooperativel (CCEVFRGS) in Santa Maria - RS, is the Home of Health hospital, whose facades are protected as a Municipal Historical and Cultural Heritage since 2002. This building stands out for the relevant provision of health services since 1932, however, it’s exterior remains at the mercy of the action of external agents. In this context, the various pathological manifestations observable in the hospital's envelope expose a high level of degradation, while strengthening the need to safeguard it. To this end, the research will be carried out through documentary and bibliographical analysis, and by on-site inspections and laboratory tests. The development of the research seeks answers to different questions in the scope of materials, techniques, building systems and, fundamentally, regarding pathological manifestations, with the damage map being the main product of this work, along with other qualitative and quantitative tests. Local inspections and non-destructive percussion tests and infrared thermography provided the information used in the damage map, while the semi-destructive tests for reconstitution of the mixture and granulometry of the aggregates added valuable data to the research for future projects of maintenance or restoration of the building's facades. Based on the damage map, the development of the Damage Measurement Method added quantitative data to the research that allow us to understand the greater or lesser incidence of pathological manifestations in function of the relationship of the facades with the surroundings, with the solar position and the alterations made by the action of man.